Genetic Studies and Selection for Ear Length of Sweet Corn (Zea Mays L.) - Woldemariam, Mandefro Nigussie (2004)
This study was conducted to investigate the effects of introgression of exotic germplasm into elite local sweet corn populations, and to determine the genetic responses to two cycles of mass and selfed progeny selections on two sweet corn populations after introgression. At the initial stage of this study, two elite local sweet corn populations (BC1-10 and BC1-9) were crossed to two exotic synthetic populations (Syn-I and Syn-II). The resulting population crosses and their parents were evaluated for performance in comparison with two check varieties. Subsequently, two superior populations, BC1-10 x Syn-II and BC2-10, which revealed high performance, were selected and used as base populations to initiate selection experiments.In the selection experiments, two cycles of mass selection (MS) and selfed progeny selection (SPS) for ear length were conducted on BC1-10 x Syn-II and BC2-10 at the Institute of Bioscience Farm, Universiti Putra Malaysia (UPM). The improved populations generated from the two base populations through MS and SPS, were evaluated with the base populations at two locations, the University Agriculture Park and the Institute of Bioscience Farm, in UPM. In BC2-10 derived populations, the predicted responses to MS were 24.7% in C1 and 18.8% in C2, whereas the predicted responses to SPS were 13.2% in C1 and 9.8% in C2. A similar trend was shown in BC1-10 x Syn-II derived populations, where the predicted responses to MS were 22.3% in C1 and 16.0% in C2, while the predicted responses to SPS were 9.9% in C1 and 8.3% in C2. The improved populations generated from the two base populations showed varied average realized responses to the two cycles of MS and SPS conducted. In BC2-10 derived populations, the realized responses to MS were 5.1% in C1 and 4.8% in C2, whereas the realized responses to SPS were 9.1% in C1 and 1.2% in C2. In BC1-10 x Syn-II derived populations, the realized responses to MS were 5.5% in C1 and 2.9% in C2, while the realized responses to SPS were 5.6% in C1 and 2.9% in C2.Based on the mean values over both locations, BC2-10 MS C2 revealed higher husked fresh ear yield (13 864 kg/ha), dehusked fresh ear yield (11115 kg/ha), husked ear length (24.6 cm), dehusked ear length (17.1 cm), husked ear diameter (46.7 mm), and number of kernels per row (42.9) than the base population (BC2-10 C0) which had mean values of 12 350 kg/ha, 10229 kg/ha, 23.7 cm, 16.0 cm, 45.1 mm and 39.1 for the same traits, respectively. A similar trend was observed on BC1-10 x Syn-II MS C2 which revealed higher dehusked fresh ear yield (10 616 kg/ha) than the base population (BC1-10 x Syn-II C0) which had 9 654 kg/ha. Ear length, which was used as the selection criterion in this study, showed high broad-sense heritability in BC2-10 and BC1-10 x Syn-II derived populations, while dehusked fresh ear yield revealed low heritability, indicating that selection for ear length if conducted on these populations in the succeeding generations would be more effective than selection for fresh ear yield. Based on data across locations, fresh ear yield showed strong positive correlations with ear length and ear diameter, indicating that, selection for any of these traits could produce improvement of fresh ear yield. The results of this study have indicated that introgression of exotic germplasm into elite local populations had effectively increased earliness in flowering, shortness of plants, kernel sweetness and yield in the population cross BC1-10 Syn-II. The two cycles of MS and SPS conducted on BC2-10 and BC1-10 x Syn-II were effective in improving ear length and some correlated traits. Further selection on these populations could offer better responses in the succeeding generations.